Membangun Fondasi Sains Sejak Dini untuk Mencetak Generasi Berpikir Kritis dan Inovatif - Elva M. Sumirat; Nurafni Surianti Haring; Gatmawati Otoluwa; Nur Amna Widya Ningsih; Indriani Indriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Early science education has a strategic role in forming critical and innovative thinking patterns in children as a provision to face challenges in the era of globalization and technological advancement. However, the implementation of the scientific approach at the early childhood education (PAUD) and elementary school levels still faces various obstacles, such as limited teacher knowledge, lack of contextual learning facilities, and teaching methods that tend to be one-way. In fact, childhood is a phase of cognitive development that is very potential to foster curiosity and scientific thinking skills. The low science literacy scores of Indonesian students in international studies indicate the need for intervention from an early age. Therefore, community service programs that aim to build a foundation for children's science from an early age are very important. This program includes teacher training, development of learning media, and exploratory activities based on simple experiments that are appropriate to the world of children. Through this approach, it is hoped that a young generation can be created who not only understand science conceptually, but also have the ability to think critically, creatively, and find solutions in facing problems in the future.